2010
DOI: 10.3892/ijmm.2010.552
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of curcumin on angiogenesis in ectopic endometrium of rats with experimental endometriosis

Abstract: Abstract. The aim of this study was to observe the inhibitory effect of curcumin on endometriosis (EMS) and to determine its influence on vascular endothelial growth factor (VEGF) and microvessel density (MVD) in eutopic and ectopic endometrium of experimental rats, thus exploring the pathogenesis of EMS offering more experimental evidence for the clinical use of curcumin. Forty-eight female virgin rats were subjected to autotransplantation of endometrium during the estrus stage. After four weeks, 8 rats were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 29 publications
4
37
1
1
Order By: Relevance
“…With the highest oral dose in use (150 mg/kg per day), ectopic glandular tissue disappeared, and VEGF expression and microvessel density were proportionately reduced. This effect was not found in eutopic endometrium (54).…”
Section: Apoptotic Agentscontrasting
confidence: 59%
See 1 more Smart Citation
“…With the highest oral dose in use (150 mg/kg per day), ectopic glandular tissue disappeared, and VEGF expression and microvessel density were proportionately reduced. This effect was not found in eutopic endometrium (54).…”
Section: Apoptotic Agentscontrasting
confidence: 59%
“…In endometriosis induced in rodents, it was capable of both preventing and treating established lesions (54,55). With the highest oral dose in use (150 mg/kg per day), ectopic glandular tissue disappeared, and VEGF expression and microvessel density were proportionately reduced.…”
Section: Apoptotic Agentsmentioning
confidence: 98%
“…[80][81][82] Similar effects on the endometriotic lesions and their vessels have been observed in the experiments testing curcumin, a pharmacological active component of Curcuma longa. 83 Puerarin (a compound isolated from Radix puerariae), Djokovic D, et …”
mentioning
confidence: 99%
“…141 Another study demonstrated that intragastrically administered curcumin exerted anti-angiogenic activity in a rat model of endometriosis by significantly reducing heterotopic endometrial microvessel quantity and VEGF translational expression. 142 …”
Section: The Renal Systemmentioning
confidence: 97%